Les travaillistes et la dévolution 1966-1999 - Carine Berberi (Revue Française de Civilisation Britannique)
From 1966 onwards the Labour Party started to change its viewpoint on devolution, becoming increasingly favourable to the creation of devolved governments in Scotland and Wales. Despite the debacle of the 1979 referendums, it continued to support devolution and ultimately succeeded in creating a Scottish Parliament and a Welsh Assembly in 1999. Why did Labour follow such a policy? Did their evolution show a genuine conversion to devolution or was it a reaction to specific economic and political circumstances, i.e., to purely pragmatic reasons?